Spatiotemporal Patterns and Population Characteristics of Harvested Wolverine (Gulo gulo) in Yukon ... - Kukka, Piia M. (University of Alberta Library, 2017)
Wolverines (Gulo gulo) are harvested for fur in Yukon, Canada, but little is known about the sustainability of their harvest. In the absence of population data, harvest management relies on harvest data to assess the efficacy of regulations and harvest sustainability. I examined the spatiotemporal patterns of wolverine harvest in Yukon from 1988 to 2015. Overall, there was no significant trend in wolverine harvest over time, but harvest patterns varied regionally. Wolverine harvest was concentrated in southwestern Yukon, where mean annual harvest rates remained high (>10%) over time, indicating that harvest is likely sustained by immigration from harvest refugia. In contrast, wolverine harvest in eastern and northern Yukon was relatively low, and estimated harvest rates (<6%) suggest sustainable local harvest. Only 13% of licensed trappers, and 16% of traplines, reported wolverine harvest in a given year, indicating that wolverine was not a focal species for many trappers. Wolverine harvest is likely ...